Teacher’s Perception towards Human Resource Development Climate: Enhancing Teacher Perception for Better Human Resource Development (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Teachers are the most important asset for the success of any university. There is a need to provide congenial HRD environment for the effectiveness of their performance. Perception of optimum level of Human Resource Development Climate is extremely important for facilitating HRD. So, the present study is based on perception of teachers towards General Climate, HRD Mechanisms and OCTAPACE Culture of HRD Climate in respect to gender classification. For this purpose, data has been collected from 117 teachers (63 females and 54 males) of private universities from two states i.e. Punjab and Haryana using “38-item HRD Climate questionnaire developed by Rao and Abraham, 1985.” The findings indicated that teachers perceive moderately good HRD Climate in the selected private universities. The perception of teachers does not differ significantly towards HRD Climate according to their gender. Hence, present study suggests that efforts should be made by management to increase the perception of teachers to above average.